2020
DOI: 10.1080/23802359.2020.1792366
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Aphis gossypii Glover, 1877 (Hemiptera: Aphididae) isolated from Plantago asiatica in Korea

Abstract: We have determined mitochondrial genome of A. gossypii isolated from Plantago asiatica in Korea. The circular mitogenome of A. gossypii is 16,045 bp including 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNAs, and a single control region of 798 bp. Its AT ratio is 83.8%. In comparison this mitogenome to Chinese and Korean A. gossypii mitogenomes, 66 single nucleotide polymorphisms (SNPs) and 176 insertions and deletions (INDELs) and 11 SNPs and 173 INDELs are identified, respectively, presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 20 publications
5
25
0
Order By: Relevance
“…Similar to the previous studies in which complete genomes were rescued from the sample containing multiple organisms (Bae et al. 2020 ; Park, Xi, Park, Lee 2020 ; Park, Xi, Park, Nam, et al. 2020 ; Oh et al.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Similar to the previous studies in which complete genomes were rescued from the sample containing multiple organisms (Bae et al. 2020 ; Park, Xi, Park, Lee 2020 ; Park, Xi, Park, Nam, et al. 2020 ; Oh et al.…”
supporting
confidence: 69%
“… 2019 ), and Plantago asiatica (Bae et al. 2020 ) have been sequenced. Here, we presented the complete mitogenome of A. gosspii isolated from Leonurus japonicus in Korea.…”
mentioning
confidence: 99%
“…Recent study of fungal mitochondrial genomes rescued from NGS raw reads of the R. speculum sample presented that it belonged to the family Ophicocordycipitaceae . It indicates that NGS sequencing is an efficient method in detecting symbionts like previous studies (Bae et al 2020;.…”
mentioning
confidence: 55%
“…A number of these identified intraspecific variations were in the large side for insect mitochondrial genomes (e.g. 11-66 SNPs and 173-176 INDELs in two Aphis gossypii mitogenomes; Bae et al 2020;Park et al 2019), although these numbers may not be suitable for direct comparison as single mutations can cause different bases of variations. Eighty-six SNPs were in PCGs, 6 were in rRNAs, 5 were in tRNAs, and the rest were in intergenic spaces, especially the A-T rich control region.…”
mentioning
confidence: 99%
“…We investigated intraspecific mitogenomic variation based on the existing mitogenome isolated from Chinese M. persicae (Yang et al 2017) and identified 30 single nucleotide polymorphisms (SNPs), 12 insertions and deletions (INDELs), and 3 large INDELs in the control region (with sizes 438, 220, and 233 bp). These intragenic variations are larger than those of Aphis gossypii Bae et al 2020), Nilaparvata lugens (Choi et al 2019; CONTACT Chungoo Park chungoo@jnu.ac. Choi et al 2020), Laodelphax striatellus , and Spodoptera frugiperda (Seo, Lee, et al 2019), but are smaller than those of Chilo suppresallis .…”
mentioning
confidence: 87%